Testing Social Media Advertising Effectiveness with Multi-Method User Experience Research - Tobias Ahnfeld; Alexander Hahn; Jan Joosten; Katharina Klug; Dirk Totzek (Marketing Review St.Gallen, 2023)
This study highlights the importance of pre-testing social media ads and explores the challenges of objectively assessing ad performance. It outlines how a multi-method approach combining facial coding and eye-tracking can help identify successful ads before launch. The findings emphasize the growing importance of user experience research (via digital empathy) for social media advertising and performance marketing.
Keywords: 650